PERSPREKTIF ASESMEN AUTENTIK SEBAGAI ALAT EVALUASI DALAM MERDEKA BELAJAR - Wiku Aji Sugiri; Sigit Priatmoko (Universitas Islam Lamongan, 2020)
The renewal of the curriculum is an important part of developing the education system in Indonesia. In this renewal, the evaluation section is one important part that must be studied in depth. The research aims to provide an authentic assessment perspective on the renewal that has just taken place, namely Merdeka Belajar. This study uses a descriptive qualitative approach, where researchers are the key to the exposure of data that has been obtained from the field. The study was conducted at SDN Model Banyuwangi with the subject of several teachers, ranging from elementary to high class. The data obtained that is, teachers at the school are able to carry out authentic assessments well. Although in the middle of the implementation there are small obstacles that arise. The authentic assessment provides a detailed assessment of students in the affective, cognitive, and psychomotor aspects. Overall, it can be agreed that the authentic assessments that have been implemented in the 2013 curriculum deserve to be integrated as an evaluation tool in the Merdeka Belajar that was just launched by the Ministry of Education and Culture. Keywords: Authentic Assessments, Merdeka Belajar